The making of economic society - Heilbroner, Robert (Englewood Cliffs, N. J. : Prentice Hall, 1993)
This text surveys the development of the market society and its problems from antiquity to the present. Designed for undergraduate courses in economic history, it intends to show how the roots of today's problems are in the past. This edition includes coverage of the collapse of Soviet communism.
Includes bibliographical references and indexes.
Keywords: Economic history